Social Work and Mothering: Mapping the Intersections of Social Work and Matricentric Feminism - Kuri, Erin; Fierheller, Dianne (Journal of the Motherhood Initiative for Research and Community Involvement, 2022)
The social construction of motherhood informs and permeates the field of social work through practice, research, and education, yet mothering experiences are often silenced in course curriculums, practice settings, and research agendas. We bring together both our voices and unique experiences as mothers, social work PhD candidates, as well as social worker and art therapist that have worked alongside mothers for many years in our professional landscapes situated in community-based and healthcare settings. Throughout this article, we argue that although the gendered nature of social work has been acknowledged by many scholars over the years—across liberal, Marxist, radical, and socialist feminist perspectives—a critical feminist analysis of mothering that incorporates maternal theory and matricentric feminism is largely absent from social work theory, research, education, and practice. We offer a historical chronological review of literature in which to contextualize current tensions and possibilities at the intersection between the profession of social work, conceptualizations of mothering within social work, and maternal feminist theory within a North American context. We aim to demonstrate how awareness of this history is a vital component of critical practice with mothers and as mothers.